(untitled) (Journal of Partial Differential Equations, 2023)
Consider (M,g) as an n-dimensional compact Riemannian manifold. In this paper we are going to study a class of elliptic differential operators which appears naturally in the study of hypersurfaces with constant mean curvature and also the study of variation theory for 1-area functional.